(untitled) (Progressive Agriculture, 2016)
The economic consequences of an outbreak of Foot and Mouth Disease (FMD) in Bangladesh is devastating. A sensitive, reliable and rapid diagnosis is crucial for the effective control of FMD. The present research was conducted for quick molecular detection and adaptation of FMD virus (FMDV) in BHK-21 (Baby Hamster Kidney) cell line. A two-step RT-PCR method was applied for the detection of the FMDV. Without prior adaption into BHK-21 cell culture, it is difficult to detect FMDV directly from the field samples by RT-PCR method. Samples were collected from the tongue epithelium (N=19) and inter digital tissues (N=4) of the suspected animals in Sujanagar, Bera, Santhia of Pabna district and Kotowali, Trishal of Mymensingh districts of Bangladesh during the year 2014. BHK-21 cell subculture was done from a previously cultured bottle containing BHK-21 cells. Prepared inocula were inoculated into BHK-21 cell culture and incubated at 37ºC for 24 h. After 36 h, cytopathic effects (CPE) were observed in BHK-21 cell line characterized by rounding and flattening of the cells, multinucleated giant cells formation, breaking down of the intracellular bridges and finally cell death indicated the presence of FMDV. Clear infectious BHK-21 cell culture fluid was collected and preserved at -20ºC temperature for virus detection by RT-PCR with serotype specific primers. Viral RNA was extracted from the clear infectious cell culture fluid for cDNA synthesis and used for PCR. Out of 23 samples tested, 3(13.04%) were positive for FMDV serotype A. The findings of this study can be helpful for the selection of vaccine having specific FMDV type, and it may help in controlling FMD in Bangladesh. Progressive Agriculture 27 (1): 64-69, 2016